Quantification of protopectinase SE, an endopolygalacturonase with pectin-releasing activity from Geotrichum klebahnii - Cavalitto, Sebastián Fernando (1999)
Pectin releasing activity of protopectinase SE (PPase-SE) from Geotrichum klebahnii (= G. penicillatum = Trichosporon penicillatum) ATCC 42397 was determined using different batches of lemon protopectin as substrate. Results obtained showed a high degree of variability depending on the batch of protopectin used. As PPase-SE also shows polygalacturonase (PGase) activity, a method for the assay of this activity was optimised. The best assay conditions were: substrate (polygalacturonic acid) concentration of 2.0 g 1−1, reaction time of 10 min and up to 0.17 PGase units per test tube.